New Insights into the Chemical and Biochemical Basis of the "Yang-Invigorating" Action of Chinese Yang-Tonic Herbs. (29th December 2014) - Chen, Jihang; Wong, Hoi Shan; Leong, Pou Kuan; Leung, Hoi Yan; Chan, Wing Man; Ko, Kam Ming
Abstract : In the practice of traditional Chinese medicine, many Yang-tonic herbs have been used for retarding the decline in bodily function and delaying the onset of age-related diseases. Our earlier studies have demonstrated that Yang-invigorating herbs/formulations protect against oxidative injury in various organs and also extend the median lifespan in mice. This lifespan extension was associated with an upregulation of cellular antioxidant status including that of mitochondria whose functional capacity is also increased by "Yang-invigorating" herbs/formulations. In this paper, we propose that triterpenes and phytosterols, which are ubiquitously found in Yang-tonic herbs, may be the chemical entities responsible for enhancing mitochondrial functional and antioxidant capacity and thus the "Yang-invigorating" action. The biochemical mechanism underlying this "Yang-invigorating" action may involve a sustained production of low levels of mitochondrial reactive oxygen species (ROS) secondary to an increased activity of the electron transport chain, with the possible involvement of mitochondrial uncoupling. The increase in mitochondrial functional capacity can retard the decline in bodily function during aging, whereas the mitochondrial ROS production is instrumental in eliciting a glutathione antioxidant response via redox-sensitive signaling pathways, which can delay the onset of age-related diseases.